2008
DOI: 10.1097/dad.0b013e318164fc87
|View full text |Cite
|
Sign up to set email alerts
|

Identical Twins With Primary Cutaneous Melanoma Presenting at the Same Time and Location

Abstract: Thus far there have been very few cases that document such a rarity as the same cancer occurring in monozygotic twins, at the same time, in the same location. We report this extraordinary phenomenon in our patients, 71-year-old identical female twins, presenting with melanoma at the same time (within 10 days of each other) and location (the right calf).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Recently, it was reported that COX-2 is strongly expressed in malignant melanoma, and may be correlated with disease development and progression. In contrast, other studies did not detect this protein in primary melanoma cells, but it was found in infiltrating inflammatory or metastatic cells (20)(21)(22).…”
Section: Discussionmentioning
confidence: 65%
“…Recently, it was reported that COX-2 is strongly expressed in malignant melanoma, and may be correlated with disease development and progression. In contrast, other studies did not detect this protein in primary melanoma cells, but it was found in infiltrating inflammatory or metastatic cells (20)(21)(22).…”
Section: Discussionmentioning
confidence: 65%
“…[7] described two identical male twins (from a set of triplets) who developed melanoma at age 53, at the same site and within a time frame of 2 months, while the fraternal triplet showed no evidence of tumour. More recently, Rao et al [8] reported two 71-year-old, identical female twins, diagnosed with melanoma at the same time (within 10 days of each other) and location (right calf). Our patients were skin type 1 as the latter pair but they were younger than both pairs.…”
Section: Discussionmentioning
confidence: 99%